2021
DOI: 10.1042/bsr20203091
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea affects in vitro porcine oocyte maturation through increased apoptosis and oxidative stress

Abstract: Hydroxyurea (HU) is an FDA-approved drug used to treat a variety of diseases, especially malignancies, but is harmful to fertility. We used porcine oocytes as an experimental model to study the effect of HU during oocyte maturation. Exposure of cumulus-oocyte complexes (COCs) to 20 µM (p < 0.01) and 50 µM (p < 0.001) HU reduced oocyte maturation. Exposure to 20 µM HU induced approximately 1.5-fold and 2-fold increases in Caspase-3 (p < 0.001) and P53 (p < 0.01) gene expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The current data revealed that HDU triggered significant hepatic inflammation and apoptosis via upregulation of TNF-α and caspase-3 apoptotic pathways expressed by the strong immunostaining of both TNF-α and Caspase-3 proteins liver tissues in HDU treated rats. These latter results are in harmony with previous studies [9] and may be explained by the DNA damage due to increased hepatic NO level [68]. In the current study, the downregulation of TNF-α and Caspase-3 expressions in the liver tissues following oral RJ co-administration reflected the RJ's anti-inflammatory and anti-apoptotic effects against HDU-induced hepatic injury.…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…The current data revealed that HDU triggered significant hepatic inflammation and apoptosis via upregulation of TNF-α and caspase-3 apoptotic pathways expressed by the strong immunostaining of both TNF-α and Caspase-3 proteins liver tissues in HDU treated rats. These latter results are in harmony with previous studies [9] and may be explained by the DNA damage due to increased hepatic NO level [68]. In the current study, the downregulation of TNF-α and Caspase-3 expressions in the liver tissues following oral RJ co-administration reflected the RJ's anti-inflammatory and anti-apoptotic effects against HDU-induced hepatic injury.…”
Section: Plos Onesupporting
confidence: 92%
“…Furthermore, it is recurrently used to treat HIV infections and sickle cell disease, polycythemia vera, and essential thrombocytopenia [1,7,8]. Although its advantageous effect, there are many reports on gonadotoxicity [3,9] cytotoxicity [10], and genotoxicity impact of HDU [11,12]. The integrated mechanism of HDU-induced gonadotoxicity (decreased sperm production and spermatogenic arrest, and reduced oocyte maturation) and cytotoxicity is explained by the overproduction of the formation of the reactive oxygen species [3,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of apoptosis was assessed using FITC Annexin V Apoptosis Detection Kit (Biolegend, California, USA), as previously described [ 27 ]. T24 and 5637 cells after different treatment were resuspended in Annexin V binding buffer at a concentration of 1.0 × 10 7 cells/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of apoptotic cells was detected as previously described [ 30 ]. U87MG and A172 cells were trypsinized and resuspended in Annexin V binding buffer (FITC-Annexin V Apoptosis Detection Kit with 7-AAD, Biolegend, California, USA) at a concentration of 1.0 × 10 6 cells/mL.…”
Section: Methodsmentioning
confidence: 99%